(untitled) (Journal of Nuclear Technology in Applied Science, 2020)
The interface between Nuclear Power Plants (NPPs) and electric gridsDeserves careful attention, especially in low-performance electric powersystems. NPP, during shutdown and startup, are in essential need to reliable electric energy that should be delivered by power grid to NPP power house.Safety systems of the NPP are designed for continuous operation with limited variations in voltage and frequency from the nominal values. Hence electrical supply voltage and frequency should also be controlled within a defined narrow range.One way to improve grid characteristics is using Capacitors devices Capacitors are placed in distribution networks with various sizes to improve voltage profile and to control reactive power. This paper proposes a method for optimization of capacitors location and sizes, to improve the voltage profile as well as reduce power losses of electric grid connecting with NPP. The proposed technique is based on genetic algorithms and applied to 16-bus radial distribution network to assure its improvement.